THE EXISTENCE OF WOMEN IN THE QĀLŪ WISDOM QUOTES ANTHOLOGY BY ANIS MANSOUR (AN EXISTENTIALIST FEMINISM REVIEW) - Alfi Mardhiyatus Staniyah; Muhammad Khoirul Malik (Arabic Literature Department, 2023)
This research concentrates on the analysis of the wisdom quotes compilation within the Qālū wisdom anthology by Anis Mansour. Among other studies on Mansour, examining this anthology of wisdom quotes is significant due to its previously unexplored nature, specifically regarding Mansour's attitude toward women as represented in this work. Utilizing a qualitative descriptive method and bibliographic technique, the study describes data related to women's existence and analyzes the data using Simone de Beauvoir's existentialist feminism approach. The findings suggest that Mansour affirms women's existence through his work by portraying more descriptions of women than men. Through these descriptions, women are shown to have superiority over men, even though in some places they are depicted as inferior. The anthology also discusses marriage, women's character, and women's liberation, which from an existentialist feminist viewpoint aligns with Simone de Beauvoir's perspective.